Microstructure and Stress Rupture Properties of K417G Superalloy at Different Hot Isostatic Pressing Temperatures - Yuanhong Lin; Lihui Zhang; Hongmin Guo (Advances in Materials Science and Engineering)
The effect of hot isostatic pressing (HIP) on the stress rupture property of K417G nickel-based superalloy is studied experimentally. The results show that the stress rupture property of the alloy is improved by the appropriate HIP process. After HIP, the average microporosity of alloy after HIP is 0.04%, which is reduced by nearly 90% compared with the as-cast microstructure. The cubic γ′ precipitates grow up, accompanied by the precipitation of the fine γ′ phase in the matrix. In addition, the area fraction of (γ + γ′) eutectic decreases, dendritic segregation is improved, and the element distribution is homogenized. As the HIP temperature increased from 1175°C to 1195°C, the microporosity and eutectic are further reduced slightly. The stress rupture life at 760°C and 645 MPa of alloys after HIP at 1175°C and 1185°C increased by 90 h and 20 h, respectively, compared with the as-cast alloy, but it is not the case for HIP at 1195°C. In addition, the elongation after HIP is increased by about 60% compared to the as-cast alloy, with an average of 4.7%. The changes in the γ′ phase and the deformation mechanism after HIP are discussed.